Monetary Policy Implementation and Financial Performance of Commercial Bank in Rwanda: A Case of Equity Bank, Rwanda - Mukundwa, Ms. Providence; Kengere, Athanas Osiemo (Journal of Finance and Accounting, 2023)
This study analyzed the effect of monetary policy implementation on the financial performance of commercial banks in Rwanda. Descriptive research design was adopted to examine how monetary policy variables affect financial performance measured by return on assets and return on Equity in Equity Bank for a period of 5 years (2017- 2021). The Study is established on loanable fund theory, New Keynes model, and classical theory of interest rate and Efficiency theory. Regression coefficient, Analysis of variance, Regression analysis, descriptive statistics (Mean and Standard deviation) and inferential (Correlation and inferential analysis) were used to estimate the joint and effect of monetary policy variables measured by interest rate, reserve requirement and liquidity management on financial performance of commercial bank . The study revealed that the endogenous variables (interest rate, reserve requirement and liquidity management) were significantly related with the dependent variable (financial performance). Thus, these independent variables strongly have an effect on the financial performance of commercial banks in Rwanda. It is concluded that monetary policy implementation has been effective for commercial banks in Rwanda by increasing their financial performance. Therefore, the Study recommended that commercial Banks should consistently adopt monetary policy implementation that will help Rwandan banks to improve on their profitability. Keywords: Monetary Policy Implementation, Financial Performance, Commercial Bank, Equity Bank, Rwanda